Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\sqrt{3}-\frac{5}{2}>\sqrt{3}-4\text{ vì }-\frac{5}{2}>-4\)
\(\Rightarrow2.\left(\sqrt{3}-\frac{5}{2}\right)>\sqrt{3}-4\)
\(\Rightarrow2.\sqrt{3}-5>\sqrt{3}-4\)
\(\left(x-5\right)\left(2x+3\right)-2x\left(x-3\right)+x-7\)
\(=\left(2x^2+3x-10x-15\right)-\left(2x^2-6x\right)+x-7\)
\(=2x^2-7x-15-2x^2+6x+x-7\)
\(=-22\)
\(\frac{\sqrt{3}+\sqrt{7}}{\sqrt{3}-\sqrt{7}}+\frac{\sqrt{3}-\sqrt{7}}{\sqrt{3}+\sqrt{7}}\)
\(=\frac{\left(\sqrt{3}+\sqrt{7}\right)\left(\sqrt{3}+\sqrt{7}\right)+\left(\sqrt{3}-\sqrt{7}\right)\left(\sqrt{3}-\sqrt{7}\right)}{\left(\sqrt{3}-\sqrt{7}\right)\left(\sqrt{3}+\sqrt{7}\right)}\)
\(=\frac{\left(\sqrt{3}+\sqrt{7}\right)^2+\left(\sqrt{3}-\sqrt{7}\right)^2}{3-7}\)
\(=\frac{3+2\sqrt{3}.\sqrt{7}+7+3-2\sqrt{3}.\sqrt{7}+7}{-4}\)
\(=\frac{3+7+3+7}{-4}\)
\(=\frac{20}{-4}=-5\)
Ta có: \(\sqrt{7-3\sqrt{5}}\)
\(=\frac{\sqrt{14-6\sqrt{5}}}{\sqrt{2}}\)
\(=\frac{\sqrt{9-2\cdot3\cdot\sqrt{5}+5}}{\sqrt{2}}\)
\(=\frac{\sqrt{\left(3-\sqrt{5}\right)^2}}{\sqrt{2}}\)
\(=\frac{\left|3-\sqrt{5}\right|}{\sqrt{2}}\)
\(=\frac{3-\sqrt{5}}{\sqrt{2}}\)(Vì \(3>\sqrt{5}\))